ANALISIS REAKSI PASAR TERHADAP KEBIJAKAN STOCK SPLIT SEKTOR PERDAGANGAN, JASA, DAN INVESTASI TAHUN 2016 - 2021 - Aldila, Exi; Kaluge, David (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to examine market reactions caused by stock split events in the trade, service and investment sectors from 2016 to 2021. This study used 13 sample companies with 5 sub-sectors as measured by the variables Trading Volume Activity, Abnormal Return and Share Transaction Value. The analysis technique used is event windows by comparing data 5 days before and 5 days after the stock split event. The analytical method used in this research is descriptive analysis, Kolmogorov-Smirnof normality test, Paired Sample T-test hypothesis testing. From these tests, the results show that there is no significant difference in Trading Volume Activity and Share Transaction Value and the data remains the same between before and after the stock split. In contrast to Abnormal Return experiencing significant differences with a decreasing probability value. This shows that the stock split event that occurred received a negative response from the market as evidenced by a decrease in Abnormal Return and no change in Trading Volume Activity and Share Transaction Value.